Evaluation of factors affecting the decision to register as a potential bone marrow donor - Branach, Beata; Tadla, Monika; Nurzyńska-Flak, Joanna (Journal of Education, Health and Sport, 2018)
Introduction. Allogenic hematopoietic stem cell transplants (HSCT) are the curative treatment for a number of hematological ailments. A number of transplants from matched unrelated donor (MUD) is increasing. The search for donors and the exchange of information in the international space is possible thanks to the global organization of the World Marrow Donor Association (WMDA) and Bone Marrow Donors Worldwide (BMDW). The DKMS is a Polish organization involved in the registration of potential bone marrow donors (PBMD). Purpose of work. The objective of the study was to assess the factors that influence the decision to register as a PBMD. Material and method. 124 people took part in the survey and filled the original questionnaire. Some of the surveys were collected during the registration of PBMD organized by the DKMS Foundation and some were filled in electronically. Questions were divided into groups. The first part concerned the determination of demographic characteristics of surveyed people. Then there were single-choice and multiple-choice questions. The results were analyzed with computer program Microsoft Excel 2011. Results. 86.3% of the respondents were women, while men - 13.7%. The majority of respondents live in cities with a population of 150 000 - 500 000 residents. 8.9% of respondents confirmed that someone from their environment required a bone marrow stem cell transplant. When asked about how fast they made the decision concerning the issue of registration as PBMD, 44.4% of the respondents made the decision on the day of the registration. Conclusion. In this group classical altruistic motives are top drivers for registering as PBMD. The knowledge about factors which influence people’s decision to become PBMD is important to target recruitment efforts.